A new institutional economic theory of project management - Yung, Ping (Journal of Business Economics and Management, 2014)
The theories of project management are not well developed despite the existence of extensive literature on the topic. This paper derives a New Institutional Economic theory of project management. It is suggested that project management encompasses both the discipline of operational management and that of economics. The operational management part deals with optimization of project processes. The basic postulation of the economic part is that human beings will maximize their benefits under constraints. Constraints are converted to either price or cost to facilitate the application of the law of demand. Three examples are used to demonstrate how refutable hypotheses can be derived when changes in constraints lead to changes in behaviours. The functions of project management are discussed in the contexts of this theoretical framework. A synthesis with existing theories is also given.